Maturity Assessment in Industry 4.0 – A Comparative Analysis of Brazilian and German Companies - Luciano Raizer Moura; Holger Kohl (Emerging Science Journal, 2020)
The article presents a comparative analysis of maturity level in Industry 4.0, of Brazilian companies with German Industry, seeking to identify learning opportunities to increase competitiveness. It was used the maturity model in Industry 4.0 developed by VDMA (German Mechanical Engineering Industry Association), applied to German companies, serving as benchmark. The same model was applied to Brazilian companies, from the State of Espírito Santo, located in the most developed region of the country, but with lower industrial density, and which has great challenges to increase its participation in the national and international markets. A field research was carried out with 46 industries, which participated in workshops to understand the fundamentals and to evaluate the maturity level in Industry 4.0. The individual results were processed by the platform of VDMA, indicating the levels in six dimensions of the model and the general result on a scale of 0 to 5. The results of all companies were tabulated, allowing the comparison with the research carried out with German companies. The study showed that, on average, Brazilian companies have the same level of maturity of German companies in readiness for Industry 4.0, with grade 0.9 in a scale of 0 to 5. But, there are significant differences in compared dimensions. 5.6% of German companies are at the advanced level in Industry 4.0, especially the technology developers, while Brazilian companies studied are still at the most basic levels. Both Industries are skeptical about investments in Industry 4.0 and the level of evaluation on Strategy dimension is still low. The comparison of expectations and difficulties allowed identify essential points to support these companies to follow the way to Industry 4.0.